Cellulose-upgraded polymer films for radiative sky cooling. (September 2021) - Chowdhury, Farsad Imtiaz; Xu, Qiwei; Sinha, Kaustubh; Wang, Xihua
Highlights: Wood derived biopolymer cellulose for radiative cooling application. Cellulose-upgraded polymer with a cooling temperature 3.97 °C below the ambient temperature at late afternoon. Maximum cooling power provided by the optimized cellulose-upgraded sample is 82.66 W/m 2 . Polycrystalline silicon solar cells operating temperature has been reduced by cellulose-upgraded polymer resulted in increased efficiency. Abstract: Radiative sky cooling reduces the temperature of an object by exchanging heat with the cold universe through the sky. Such radiative cooling mechanism exists in nature but with lower cooling efficiency. For effective radiative cooling, the surface of an object should have high reflectivity in the solar spectrum and high emissivity in Earth's atmospheric transparent window (8-13 µm). In this work, we report a new class of radiative sky cooling material – cellulose-upgraded polymer films. This sample has low absorption in the solar spectrum and high emissivity in the mid-infrared region. When exposed to direct sunlight, this optimized sample cools to 3.97 °C below the ambient temperature and has a cooling power of 82.66 W/m 2 during the late afternoon. Placing this sample in direct contact with a silicon solar cell shows a reduction in operating temperature under direct sunlight that can enhance the power output from the cell. This approach can easily be applied to large areas at a low cost and is a significant step forward for the large-scale application of radiative cooling technology.